Pembinaan Atlet Muda Bulutangkis dengan Kejuaraan UNIBA CUP III Se-Karesidenan Besuki Tahun 2023 - Wawan Setiawan; Marki Sandi; Supono Supono; Yuni Fitriyah Ningsih (Laksana Olahraga, 2023)
Abstract: Badminton is a sport that is very popular with the community both as a daily sport and as a professional sport by many young Indonesians. This can be seen from the many young badminton athletes who have emerged and are also supported by Indonesia's badminton achievements on the world stage which are very proud of. With the achievements of these very good Indonesian athletes and to further maintain the competition for badminton achievements on the international stage, we PGRI Banyuwangi University intend to hold a SMA / SMK / MA Badminton Championships throughout Besuki Raya "UNIBA CUP III 2023". It is intended that potential young athletes have a place to improve techniques, tactics, mentally and physically playing badminton. In this championship, young athletes will gain sufficient playing experience, as well as become a place to train their minds, tactics and physically in taking part in badminton championships. In our service activities, we carried out several stages, including the preparation stage, including the socialization of the badminton championship by distributing invitation letters and championship brochures to SMA / SMK / MA throughout the Besuki Residency. Furthermore, to record the players who have registered both offline and online and the last is the technical meeting, after that the championship implementation stage is carried out for 5 days and the last is the final evaluation stage, namely making a final report. The participants who took part in the Uniba CUP III badminton championship totaled 105 athletes who took part in several competition numbers, namely men's singles, women's singles, men's doubles and mixed doubles. This championship is held in a knockout system starting from the top 64 for men's singles, and the top 32 for women's singles, men's doubles and mixed doubles. Based on the results of the community service activities that have been carried out, (1) the players have a good place to train the mentality of competing in official championships, (2) the trainer has an overview to provide evaluations to the athletes regarding the right techniques, tactics and strategies for each athlete, so as to then can provide the right training program for them, (3) for the committee who are Penjaskesrek students, have experience in match management and experience in refereeing.